Effect of Amount of Cutting Fluid on Surface Finish of Turned Parts - Islam, Mohammad Nazrul (Trans Tech Publications Ltd., 2011)
This paper presents the experimental and analytical results of the effect that the amount of cutting fluid has on the surface finish of turned parts. The experiments were planned using Taguchi’s orthogonal array methodology. A three-level, four-parameter orthogonal array (L81) was selected for designing the experiments. The selected four input parameters are cutting speed, feed rate, depth of cut, and amount of cutting fluid. Mild steel AISI 1030 was chosen as the work material. A total of 81 experimental runs were conducted, and the surface roughness parameter arithmetic average was measured offline using a surface finish analyzer. Subsequently, the results were analyzed applying three methods—traditional analysis, Pareto ANOVA, and the Taguchi method. The results indicate that the amount of cutting fluid has a negligible effect on surface finish. However, the interaction between the two major contributors—cutting speed and feed rate—is influenced noticeably by the amount of cutting fluid.